2010
DOI: 10.1177/0899764010371232
|View full text |Cite
|
Sign up to set email alerts
|

Is the Third Sector an Emerging Economic Institution? Social Preferences Versus Poverty Traps

Abstract: Relying on social preference theory and on poverty trap literature, this article\ud suggests a richer and more nuanced role of the third sector as an institution\ud complementary to the state and to the market in an economy’s development\ud process. Social preferences are considered as the micro—fundaments of the third\ud sector in that this promotes activities, laws, and organizational forms coherent with\ud those preferences. The third sector contributes to overcoming poverty traps not\ud only by spreading b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Explicit scope, community dedication SR_1 [94,95] Budget and financial transparency SR_2 [96][97][98] Decision making is not based on NPO equity SR_3 [94,99] Stakeholder involvement in financial decisions SR_4 [100] High number of volunteers SR_5 [73] Data analysis was performed using the SPSS statistical software. We used univariate and bivariate analysis methods and tested the validity and consistency of the model using statistical hypothesis testing and research.…”
Section: Economic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Explicit scope, community dedication SR_1 [94,95] Budget and financial transparency SR_2 [96][97][98] Decision making is not based on NPO equity SR_3 [94,99] Stakeholder involvement in financial decisions SR_4 [100] High number of volunteers SR_5 [73] Data analysis was performed using the SPSS statistical software. We used univariate and bivariate analysis methods and tested the validity and consistency of the model using statistical hypothesis testing and research.…”
Section: Economic Resultsmentioning
confidence: 99%
“…In addition to mission completion, good financial performance has become more relevant to NPOs during the past decades [95,96]. Furthermore, commercialization of the non-profit sector has increased [97,98]. From this perspective, organizational survival becomes the prerequisite for mission accomplishment, and researchers have even suggested that survival is the ultimate criterion on which NPO success should be evaluated [99].…”
Section: Accounting Ratios Rejectedmentioning
confidence: 99%
“…Voluntary work provides a wide range of benefits to the volunteer but also to the social group, community, and society where this behavior takes place. It has been shown that the volunteers themselves can share in the positive effects of their actions (Taylor, 2004;Ronel, 2006;Amendola et al, 2011;Binder and Freytag, 2013). Given the positive influence of civil and community associational activities, policy-makers should promote the development and consolidation of high levels of social capital (Sabatini, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Coupled with an increased marketization of the non-profit sector [86], it makes some scholars consider survival as the ultimate criterion on which NPO success should be evaluated in terms of success and therefore sustainability [9].…”
Section: Sustainability Approaches In Non-profit Organizationsmentioning
confidence: 99%
“…All items were extracted from studies addressing non-profit sustainability [31,46,53,[84][85][86]100]. For the Small number of employees variable we used a previous study on Romanian non-profits [101], which allow us to consider that, if the NPO has less than 10 employees in the last year will receive a 0 on measurement scale and, conversely, 1 for the other instance.…”
Section: Dependent Variablementioning
confidence: 99%